COVID-19-Related Fear and Health-Related Safety Behavior in Oncological Patients - Musche, Venja; Bäuerle, Alexander; Steinbach, Jasmin; Schweda, Adam; Hetkamp, Madeleine; Weismüller, Benjamin; Kohler, Hannah; Beckmann, Mingo; Herrmann, Ken; Tewes, Mitra; Schadendorf, Dirk; Skoda, Eva-Maria; et al. (Frontiers in Psychology, 2020)
Objective: This study aimed to assess cancer patients’ psychological burden during the COVID-19 pandemic by investigating distress (distress-thermometer), health status (EQ-5D-3L), general anxiety (GAD-7), COVID-19-related fear and associated behavioral changes and comparing these to matched healthy controls, using propensity score matching (PSM). Methods: During the first days of the COVID-19 pandemic in Germany, March 16 to 30, 2020, 150 actually treated cancer patients and 150 matched healthy controls participated in this study. Participants completed an anonymous online survey assessing health status, distress, general anxiety, COVID-19-related fear and behavioral changes (i.e. adherent safety behavior and dysfunctional safety behavior). Results: Cancer patients showed no elevated level of distress, U = 10657.5, p = .428, general anxiety U = 10015.5, p = .099, or COVID-19-related fear compared to healthy controls, U = 10948, p = .680. Both groups showed elevated COVID-19-related fear. Cancer patients reported more adherent safety behavior, such as washing hands more often or avoiding public places, U = 8285, p < .001, d = 0.468. They also reported more dysfunctional safety behavior such as buying larger quantities of basic food, compared to healthy controls U = 9599, p = .029, d = 0.256. Adherent safety behavior could be significantly explained by cancer diagnosis, increased COVID-19-related fear and subjective level of information about COVID-19, R² = .215 (F(3) = 27.026, p < .001. Conclusions: This suggests that cancer patients are more likely to utilize adherent safety behavior. Cancer patients reported comparable levels of distress and anxiety compared to healthy controls. Still, the COVID-19 pandemic is associated with elevated COVID-19-related fear. Therefore, specific interventions are needed to prevent anxiety and improve mental health during the COVID-19 pandemic.